Active surveillance inclusion criteria under scrutiny in magnetic resonance imaging-guided prostate biopsy: a multicenter cohort study - Kornienko, Kira; Siegel, Fabian; Borkowetz, Angelika; Hoffmann, Manuela A.; Drerup, Martin; Lieb, Verena; Bruendl, Johannes; Hoefner, Thomas; Cash, Hannes; Von Hardenberg, Jost; Westhoff, Niklas (Prostate Cancer and Prostatic Diseases, 2021)
Background Although multiparametric magnetic resonance imaging (mpMRI) is recommended for primary risk stratification and follow-up in Active Surveillance (AS), it is not part of common AS inclusion criteria. The objective was to compare AS eligibility by systematic biopsy (SB) and combined MRI-targeted (MRI-TB) and SB within real-world data using current AS guidelines. Methods A retrospective multicenter study was conducted by a German prostate cancer (PCa) working group representing six tertiary referral centers and one outpatient practice. Men with PCa and at least one MRI-visible lesion according to Prostate Imaging Reporting and Data System (PI-RADS) v2 were included. Twenty different AS inclusion criteria of international guidelines were applied to calculate AS eligibility using either a SB or a combined MRI-TB and SB. Reasons for AS exclusion were assessed. Results Of 1941 patients with PCa, per guideline, 583-1112 patients with PCa in both MRI-TB and SB were available for analysis. Using SB, a median of 22.1% (range 6.4-72.4%) were eligible for AS. Using the combined approach, a median of 15% (range 1.7-68.3%) were eligible for AS. Addition of MRI-TB led to a 32.1% reduction of suitable patients. Besides Gleason Score upgrading, the maximum number of positive cores were the most frequent exclusion criterion. Variability in MRI and biopsy protocols potentially limit the results. Conclusions Only a moderate number of patients with PCa can be monitored by AS to defer active treatment using current guidelines for inclusion in a real-world setting. By an additional MRI-TB, this number is markedly reduced. These results underline the need for a contemporary adjustment of AS inclusion criteria.
CRIS-Team WoS Importer:2021-12-31

Analysis of the Impact of Clinical Factors on Low-Intensity Extracorporeal Shockwave Therapy for Erectile Dysfunction - Oginski, Natalie; Apel, Hendrik; Richterstetter, Mario; Lieb, Verena; Fiebig, Christian; Goebell, Peter; Wullich, Bernd; Sikic, Danijel (Urologia Internationalis, 2022)
Introduction: Predictive factors for the treatment success of low-intensity extracorporeal shockwave therapy (Li-ESWT) for erectile dysfunction (ED) are still under debate. Methods: Li-ESWT was performed in 50 patients suffering from ED by applying 3,000 shock waves once a week over a period of 6 weeks. Treatment success was defined as an increase in the International Index of Erectile Function 5 (IIEF-5) score by >= 5 points or an Erectile Hardness Score (EHS) of >= 3 points. IIEF-5 and EHS were measured at baseline and at 3 and 6 months of follow-up. Results: Treatment success according to either the IIEF-5 score or EHS at any time of follow-up was achieved in 28 patients (56%). Twenty-five patients (50%) experienced an improvement during the first 3 months, which lasted for 6 months in 8 cases (16%). Three patients reported improved erectile function only after 6 months. When stratifying the cohort with regard to potential influencing factors, a significantly improved IIEF-5 score could be achieved in men with cardiovascular risk factors (p = 0.026) and in men with antihypertensive medication (p = 0.009). Men without cardiovascular risk factors showed no therapeutic benefit from Li-ESWT. Discussion/Conclusion: Li-ESWT is a valid but often short-lived treatment option for ED, especially in men with cardiovascular risk factors or controlled hypertension. Future studies should assess the feasibility and safety of repeated applications of Li-ESWT.
CRIS-Team WoS Importer:2022-03-04

Cell-Free DNA Sequencing Reveals Gene Variants in DNA Damage Repair Genes Associated with Prognosis of Prostate Cancer Patients - Lieb, Verena; Abdulrahman, Amer; Weigelt, Katrin; Hauch, Siegfried; Gombert, Michael; Guzman, Juan; Bellut, Laura; Goebell, Peter; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (Cells, 2022)
In the present study, we further analyzed the data obtained in our previous study, where we investigated the cell-free DNA (cfDNA) of 34 progressive prostate cancer patients via targeted sequencing. Here, we studied the occurrence and prognostic impact of sequence variants according to their clinical pathological significance (CPS) or their functional impact (FI) in 23 DNA damage repair (DDR) genes with a focus on the ATM serine/threonine kinase gene (ATM). All patients had at least one DDR gene with a CPS or FI variant. Kaplan-Meier analysis indicated that the group with a higher number of CPS variants in DDR genes had a shorter time to treatment change (TTC) compared to the group with a lower number of CPS variants (p = 0.038). Analysis of each DDR gene revealed that CPS variants in the ATM gene and FI variants in the nibrin (NBN) gene showed a shorter TTC (p = 0.034 and p = 0.042). In addition, patients with CPS variants in the ATM gene had shorter overall survival (OS; p = 0.022) and disease-specific survival (DSS; p = 0.010) than patients without these variants. Interestingly, patients with CPS variants in seven DDR genes possessed a better OS (p = 0.008) and DSS (p = 0.009), and patients with FI variants in four DDR genes showed a better OS (p = 0.007) and DSS (p = 0.008). Together, these findings demonstrated that the analysis of cfDNA for gene variants in DDR genes provides prognostic information that may be helpful for future temporal and targeted treatment decisions for advanced PCa patients.
CRIS-Team Scopus Importer:2022-12-02
Keywords: ATM; cfDNA; DDR genes; NBN; prognosis; prostate cancer; sequence variants

Cell-free dna variant sequencing using plasma and ar-v7 testing of circulating tumor cells in prostate cancer patients - Lieb, Verena; Bellut, Laura; Abdulrahman, Amer; Weigelt, Katrin; Hauch, Siegfried; Gombert, Michael; Guzman, Juan; Goebell, Peter; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (Cells, 2021)
Prostate cancer (PCa) is the second most common malignant cancer and is a major cause of morbidity and mortality among men worldwide. There is still an urgent need for biomarkers applicable for diagnosis, prognosis, therapy prediction, or therapy monitoring in PCa. Liquid biopsies, including cell-free DNA (cfDNA) and circulating tumor cells (CTCs), are a valuable source for studying such biomarkers and are minimally invasive. In our study, we investigated the cfDNA of 34 progressive PCa patients, via targeted sequencing, for sequence variants and for the occurrence of CTCs, with a focus on androgen receptor splice variant 7 (AR-V7)-positive CTCs. The cfDNA content was associated with overall survival (OS; p = 0.014), disease-specific survival (DSS; p = 0.004), and time to treatment change (TTC; p = 0.001). Moreover, when considering all sequence variants grouped by their functional impact and allele frequency, a significant association with TTC (p = 0.017) was observed. When investigating only pathogenic or likely pathogenic gene variants, variants of the BRCA1 gene (p = 0.029) and the AR ligand-binding domain (p = 0.050) were associated with a shorter TTC. Likewise, the presence of CTCs was associated with a shorter TTC (p = 0.031). The presence of AR-V7-positive CTCs was associated with TTC (p < 0.001) in Kaplan–Meier analysis. Interestingly, all patients with AR-V7-positive CTCs also carried TP53 point mutations. Altogether, analysis of cfDNA and CTCs can provide complementary information that may support temporal and targeted treatment decisions and may elucidate the optimal choice within the variety of therapy options for advanced PCa patients.
CRIS-Team Scopus Importer:2021-11-26
Keywords: CfDNA; CTCs; Prognosis; prostate cancer; Sequence variants

Combination of GP88 Expression in Tumor Cells and Tumor-Infiltrating Immune Cells Is an Independent Prognostic Factor for Bladder Cancer Patients - Eckstein, Markus; Lieb, Verena; Jung, Rudolf; Sikic, Danijel; Weigelt, Katrin; Stöhr, Robert; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; Serrero, Ginette; Yue, Binbin; Hartmann, Arndt; et al. (Cells, 2021)
Urothelial bladder cancer (BCa) is the ninth most commonly diagnosed cancer worldwide and accounts for approximately 3% of global cancer diagnoses. We are interested in prognostic markers that may characterize tumor cells (TCs) and immune cells (ICs) and their relationship in BCa. A potential candidate marker that meets these criteria is progranulin (GP88), which is expressed separately in TCs and ICs. We analyzed GP88 expression by immunohistochemistry (IHC) in 196 muscle-invasive BCa samples using a tissue microarray. The immunoreactive score for GP88 staining in TCs and the percentage of GP88-positive ICs was determined. An easy cutoff for the staining status of TCs (positive vs. negative) and ICs (0% vs. >0%) and, more generally, negative vs. positive GP88 staining could be applied. We detected 93 patients (47.4%) and 92 patients (46.9%) with GP88-positive TCs or ICs, respectively. The IHC results were correlated with clinicopathological and survival data. Positive GP88 staining in TCs appeared to be an independent poor prognostic factor for disease-specific survival (DSS) (RR (relative risk) = 1.74; p = 0.009) and recurrence-free survival (RFS) (RR = 1.92; p = 0.002). In contrast, negative GP88 staining in ICs was an independent negative predictor for overall survival (OS) (RR = 2.18; p < 0.001), DSS (RR = 2.84; p < 0.001) and RFS (RR = 2.91; p < 0.001) in multivariate Cox's regression analysis. When combining GP88 staining in TCs and ICs, a specific combination of GP88-positive TCs and GP88-negative ICs was associated with a 2.54-fold increased risk of death, a 4.21-fold increased risk of disease-specific death and a 4.81-fold increased risk of recurrence compared to GP88-negative TCs and GP88-positive ICs. In summary, GP88 positivity in TCs is a negative prognostic factor for DSS and RFS. In addition, GP88 positivity can mark ICs that are associated with a good prognosis (OS, DSS and RFS). The combination of GP88 staining in TCs and ICs appears to be a significant independent prognostic biomarker in muscle-invasive BCa.
CRIS-Team WoS Importer:2021-08-06

Combined miR-486 and GP88 (Progranulin) Serum Levels Are Suggested as Supportive Biomarkers for Therapy Decision in Elderly Prostate Cancer Patients - Fichte, Alexander; Neumann, Anna-Dorothea; Weigelt, Katrin; Guzman, Juan; Jansen, Thilo; Keinert, Julia; Serrero, Ginette; Yue, Binbin; Stöhr, Robert; Greither, Thomas; Hartmann, Arndt; Wullich, Bernd; et al. (Life, 2022)
Our study aimed to assess the applicability of miR-486 in combination with soluble GP88 protein as a diagnostic and/or predictive biomarker for prostate cancer (PCa) patients. miR-486 and GP88 levels in serum samples from 136 patients undergoing MRI-guided biopsy of the prostate were assessed by qRT–PCR and ELISA, respectively. Of these, 86 patients received a histologically confirmed diagnosis of PCa. Neither marker showed an association with the diagnosis of cancer. PCa patients were separated based on (i) treatment into patients with active surveillance or patients with any type of curative treatment and (ii) age into elderly (>68 years) patients and younger patients (≤68 years). In elderly patients (N = 41) with the intention of curative treatment at optimized cut-off values, significantly higher GP88 levels (p = 0.018) and lower miR-486 levels (p = 0.014) were observed. The total PSA level and ISUP biopsy grade were used in a baseline model for predicting definitive therapy. The baseline model exhibited an area under the curve (AUC) of 0.783 (p = 0.005). The addition of the serum biomarkers miR-486 and GP88 to the baseline model yielded an improved model with an AUC of 0.808 (p = 0.002). Altogether, combined miR-486 and GP88 serum levels are associated with and are therefore suggested as supportive biomarkers for therapy decisions, particularly in elderly PCa patients.
CRIS-Team Scopus Importer:2022-06-03
Keywords: age; miRNAs; predictive biomarker; progranulin; prostate cancer; serum level

Efficacy of cabazitaxel in fourth or later line of therapy in metastatic castration-resistant prostate cancer: Multi-institutional real-world experience in Germany - Wenzel, Mike; Borkowetz, Angelika; Lieb, Verena; Hoffmann, Manuela A.; Borgmann, Hendrik; Höfner, Thomas; Dotzauer, Robert; Neuberger, Manuel; Worst, Thomas S.; von Hardenberg, Jost; Linxweiler, Johannes; Klümper, Niklas (Urologic Oncology-Seminars and Original Investigations, 2022)
Objective: Since multiple oncological treatment options in metastatic castration-resistant prostate cancer (mCRPC) are available, optimal sequencing of therapies are under investigation. However, the efficacy of Cabazitaxel (CAB) in fourth and later lines of therapy is rarely investigated. Material and Methods: Fifty three patients with mCRPC treated with CAB in fourth line or later were included in our retrospective study, which involved eight uro-oncology centers in Germany. Clinical and tumor characteristics, as well as PSA-response rates were analyzed. Kaplan-Meier plots addressed overall survival (OS) and progression-free survival (PFS). Logistic regression models predicted risk factors of overall mortality (OM). Results: Of 53 patients, 79% (n=42), 19% (n=10) and 2% (n=1) received CAB in fourth, fifth and sixth line. A median of 4 cycles of CAB were administered. Median PSA at start of CAB was 199ng/ml (interquartile range (IQR) 70-869). In total, 89% had bone and 40% visceral metastases prior to the start of CAB. Moreover, 30% of patients received Docetaxel in first line therapy for mCRPC. Most frequent sequence of therapy was abiraterone followed by docetaxel and followed by enzalutamide. Overall, median PSA-response rate was -20% (IQR -80 to +10%). Patients with docetaxel in first line had a significantly better median PSA-response on CAB (-80 vs. 20%, P=0.03). Median OS, radiographic PFS and overall PFS were 14.8 (Confidence interval (CI): 11.0–20.8), 3.0 (CI: 2.9–4.0) and 2.9 (CI: 2.0–3.3) months, respectively. In multivariable analyses, visceral metastases, PSA >100ng/ml, ISUP4+5 and later administration of Docetaxel were predictors of OM. Conclusion: Real-world experiences indicate that favorable oncologic outcomes can be achieved with CAB especially regarding PSA-response and OS even in the fourth line or later in patients with mCRPC.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Cabazitaxel; Castration resistant; Chemotherapy; CRPC; Metastatic; Prostate cancer; Sequential therapy

Experimental in vitro, ex vivo and in vivo models in prostate cancer research - Sailer, Verena; von Amsberg, Gunhild; Duensing, Stefan; Kirfel, Jutta; Lieb, Verena; Metzger, Eric; Offermann, Anne; Pantel, Klaus; Schuele, Roland; Taubert, Helge; Wach, Sven; Perner, Sven; et al. (NAT REV UROL, 2022)
Androgen deprivation therapy has a central role in the treatment of advanced prostate cancer, often causing initial tumour remission before increasing independence from signal transduction mechanisms of the androgen receptor and then eventual disease progression. Novel treatment approaches are urgently needed, but only a fraction of promising drug candidates from the laboratory will eventually reach clinical approval, highlighting the demand for critical assessment of current preclinical models. Such models include standard, genetically modified and patient-derived cell lines, spheroid and organoid culture models, scaffold and hydrogel cultures, tissue slices, tumour xenograft models, patient-derived xenograft and circulating tumour cell eXplant models as well as transgenic and knockout mouse models. These models need to account for inter-patient and intra-patient heterogeneity, the acquisition of primary or secondary resistance, the interaction of tumour cells with their microenvironment, which make crucial contributions to tumour progression and resistance, as well as the effects of the 3D tissue network on drug penetration, bioavailability and efficacy.
CRIS-Team Scopus Importer:2022-12-16

Expression of AR-V7 (Androgen receptor variant 7) protein in granular cytoplasmic structures is an independent prognostic factor in prostate cancer patients - König, Paul; Eckstein, Markus; Jung, Rudolf; Abdulrahman, Amer; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Hayashi, Jun; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; et al. (Cancers, 2020)
Prostate cancer (PCa) is the second most common cancer, causing morbidity and mortality among men world-wide. The expression of the androgen receptor (AR) and its splice variants is a crucial factor of prostate cancer biology that has not been comprehensively studied in PCa tumors. The aim of this study was to characterize the protein expression of the AR and its splice variant, AR-V7, and their subcellular distributions in PCa by immunohistochemistry and to correlate the results to the clinicopathological data and prognosis. Immunohistochemical staining for AR and AR-V7 was performed on a tissue microarray (TMA) with specimens from 410 PCa patients using an immunoreactive score (IRS) or only the percentage of AR-V7 staining in cytoplasmic granules. Nuclear or cytoplasmic AR staining was not associated with prognosis. AR-V7 staining was only occasionally observed in the nucleus. However, AR-V7 staining in the cytoplasm or in cytoplasmic granules was associated with relapse-free survival (RFS). AR-V7 staining of the cytoplasm was associated with a shorter RFS, whereas AR-V7 staining of cytoplasmic granules was associated with a longer RFS. In a multivariate Cox’s regression analysis, only negative (<5%) AR-V7 staining of cytoplasmic granules remained an independent prognostic factor for RFS (HR = 5.3; p = 0.006). In a further subgroup analysis by multivariate Cox’s regression analysis, AR-V7 was an independent prognostic factor in the following groups: age ≤ 65 (HR = 9.7; p = 0.029), negative CK20 staining (HR = 7.0; p = 0.008), and positive perineural invasion (HR = 3.7; p = 0.034). Altogether, AR-V7 protein in granular cytoplasmic structures is an independent prognostic factor for RFS in PCa patients.
CRIS-Team Scopus Importer:2020-09-25
Keywords: AR; AR-V7; Gleason score; Perineural invasion; Prognosis; Prostate cancer; Relapse-free survival; RFS

Immune Cell-Associated Protein Expression Helps to Predict Survival in Muscle-Invasive Urothelial Bladder Cancer Patients after Radical Cystectomy and Optional Adjuvant Chemotherapy - Taubert, Helge; Eckstein, Markus; Epple, Elena; Jung, Rudolf; Weigelt, Katrin; Lieb, Verena; Sikic, Danijel; Stöhr, Robert; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; Kehlen, Astrid; et al. (Cells, 2021)
Bladder cancer (BCa) is the tenth most commonly diagnosed malignant cancer worldwide. Although adjuvant chemotherapy following radical cystectomy is a common therapy for muscle invasive bladder cancer patients, no applicable biomarkers exist to predict which patients will benefit from chemotherapy. In this study, we examined three immune cell markers, the chemokine CC motif ligand 2 (CCL2), the pan macrophage marker cluster of differentiation 68 (CD68) and the M2 macrophage marker cluster of differentiation 163 (CD163), using immunohistochemistry to determine their predictive value for the chemotherapy response in different nodal stage (pN0 vs. pN1 + 2) and tumor stage subgroups (pT2 vs. pT3 + 4). The prognosis was studied in terms of the overall survival (OS), disease-specific survival (DSS), and recurrence-free-survival (RFS) in 168 muscle invasive BCa patients. Chemotherapy was associated with a poorer prognosis in patients with a higher expression of the immune markers CCL2 (RFS), CD68 (DSS and RFS), and CD163 (DSS and RFS) in the N0 group and with poorer survival in patients with a higher expression of the immune markers CCL2 (OS, DSS, and RFS), CD68 (OS, DSS, and RFS), and CD163 (OS, DSS, and RFS) in the pT2 group when compared with treatments without chemotherapy. In contrast, chemotherapy was associated with a better prognosis in patients with a low expression of the immune markers CCL2 (DSS and RFS), CD68 (OS, DSS, and RFS), and CD163 (OS) in the N1 + 2 group. In addition, chemotherapy was associated with improved survival in patients with a low expression of the immune marker CD68 (OS and DSS) and there was a trend for a better prognosis in patients with a low expression of CD163 (OS) in the pT3 + 4 group compared to patients not treated with chemotherapy. Interestingly, CD68 appeared to be the most applicable immune marker to stratify patients by the outcome of chemotherapy in the nodal stage and tumor stage groups. Overall, we suggest that, in addition to the clinical factors of tumor stage and nodal stage, it is also meaningful to consider the abundance of immune cells, such as macrophages, to better predict the response to chemotherapy for BCa patients after radical treatment.
CRIS-Team Scopus Importer:2021-02-12
Keywords: bladder cancer; CCL2; CD163; CD68; chemotherapy; immune cells; nodal stage; tumor stage

Immunohistochemical analysis of sex hormone receptors in squamous changes of the urothelium. - Seitz, Julia; Hoegel, Josef; Eckstein, Markus; Lieb, Verena; Wullich, Bernd; Hartmann, Arndt; Rieker, Ralf (International Journal of Clinical and Experimental Pathology, 2022)
OBJECTIVE: Squamous cell transformation of the urinary bladder urothelium has various causes, symptoms, and few treatment options. The aim of this study was to analyze and compare the expression of sex hormone receptors in non-keratinized and keratinized squamous metaplasia (NKSM, KSM), squamous cell carcinoma (SCC), and healthy urothelium with regard to possible therapeutic approaches. METHODS: Biopsies from 26 patients with urothelial NKSM, KSM, and SCC were analyzed retrospectively. Tissue microarrays (TMA) of formalin-fixed paraffin-embedded (FFPE) bladder biopsies were stained with hematoxylin and eosin followed by immunohistochemical analysis with specific antibodies against estrogen, progesterone, and androgen receptors (ER, PR, AR) and assessment using the immunoreactive score. Statistical evaluations included the Wilcoxon signed-rank test and the Wilcoxon rank-sum test in the form of permutation tests. RESULTS: Of the 15 women and 11 men included in this explorative study, 17 had metaplasia: 15 (six men, nine women) had NKSM and two KSM (both men). A total of nine patients (three men, six women) had keratinized SCC or urothelial carcinoma with squamous differentiation. The comparison between normal urothelial cells and metaplasia showed a significantly stronger expression in the metaplastic tissue (P=0.0374). The invasive carcinoma showed significantly less PR than the extracellular matrix of the healthy urothelium (P=0.0026). Expression of AR was nearly absent in healthy and metaplastic urothelium. CONCLUSION: There appears to be an association between squamous metaplasia of the bladder mucosa and sex steroid hormone receptor expression, especially estrogen receptors. Topical hormone therapy should be considered.
EVALuna2:512116

Immunohistochemical analysis of sex hormone receptors in squamous changes of the urothelium - Seitz, Julia; Hogel, Josef; Eckstein, Markus; Lieb, Verena; Wullich, Bernd; Hartmann, Arndt; Rieker, Ralf (International Journal of Clinical and Experimental Pathology, 2022)
Objective: Squamous cell transformation of the urinary bladder urothelium has various causes, symptoms, and few treatment options. The aim of this study was to analyze and compare the expression of sex hormone receptors in non-keratinized and keratinized squamous metaplasia (NKSM, KSM), squamous cell carcinoma (SCC), and healthy urothelium with regard to possible therapeutic approaches. Methods: Biopsies from 26 patients with urothelial NKSM, KSM, and SCC were analyzed retrospectively. Tissue microarrays (TMA) of formalin-fixed paraffinembedded (FFPE) bladder biopsies were stained with hematoxylin and eosin followed by immunohistochemical analysis with specific antibodies against estrogen, progesterone, and androgen receptors (ER, PR, AR) and assessment using the immunoreactive score. Statistical evaluations included the Wilcoxon signed-rank test and the Wilcoxon rank-sum test in the form of permutation tests. Results: Of the 15 women and 11 men included in this explorative study, 17 had metaplasia: 15 (six men, nine women) had NKSM and two KSM (both men). A total of nine patients (three men, six women) had keratinized SCC or urothelial carcinoma with squamous differentiation. The comparison between normal urothelial cells and metaplasia showed a significantly stronger expression in the metaplastic tissue (P=0.0374). The invasive carcinoma showed significantly less PR than the extracellular matrix of the healthy urothelium (P=0.0026). Expression of AR was nearly absent in healthy and metaplastic urothelium. Conclusion: There appears to be an association between squamous metaplasia of the bladder mucosa and sex steroid hormone receptor expression, especially estrogen receptors. Topical hormone therapy should be considered.
CRIS-Team WoS Importer:2022-09-30

Kidney transplantation in prostate cancer patients after local therapy with curative intent: a systematic review - Rumpff, C.; Lieb, Verena; Wullich, Bernd; Schiffer, Mario; Kunath, Frank; Apel, Hendrik (World Journal of Urology, 2024)
Purpose: It is still unclear whether kidney transplantation can be safely performed in patients with prostate cancer after local therapy with curative intent. Methods: The protocol was registered in PROSPERO. We systematically searched Google, MEDLINE, the Cochrane Library, and the ICTRP for studies, official standards, clinical practice guidelines and organ transplant laws. Two review authors independently examined the full-text reports and identified relevant studies and one review author extracted the data. We assessed the overall certainty of the evidence for each outcome according to the GRADE approach. Results: We identified 1346 references through electronic database searching and finally included 6 references for official standards, clinical practice guidelines, and organ transplant laws, and 6 references for retrospective studies with very low certainty of evidence. We identified no prospective or ongoing studies and reported all results narratively. Conclusion: We recommend that decisions on kidney transplantation in patients with prostate cancer after local therapy with curative intent should be made on a case-by-case basis. It is indispensable to consult with health care professionals or specialists at transplant centers to obtain individualized information regarding the waiting time requirements for renal transplantation in prostate cancer patients after local therapy with curative intent. No recommendation can be made regarding the waiting times after prostate cancer therapy with curative intent.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Kidney transplantation; Prostatic neoplasms; Surgical techniques; Systematic review

Potential Candidates for Focal Therapy in Prostate Cancer in the Era of Magnetic Resonance Imaging–targeted Biopsy: A Large Multicenter Cohort Study - von Hardenberg, Jost; Borkowetz, Angelika; Siegel, Fabian; Kornienko, Kira; Westhoff, Niklas; Jordan, Tobias B.; Hoffmann, Manuela; Drerup, Martin; Lieb, Verena; Taymoorian, Kasra; Schostak, Martin; Ganzer, Roman; et al. (European Urology Focus, 2020)
Background: Focal therapy (FT) with its favorable side-effect profile represents an option between active surveillance and traditional whole-gland treatment in localized prostate cancer (PCa). Consensus statements recommend eligibility criteria based on magnetic resonance imaging (MRI)-targeted and systematic combination biopsy. Objective: To estimate the future potential of FT by analyzing the number of men eligible for FT among all men with biopsy-proven PCa and to judge the potential of different energy sources. Design, setting, and participants: Consensus criteria on FT were analyzed. Patients with biopsy-proven PCa from six tertiary referral hospitals and one outpatient practice in Germany had received a software-based combination biopsy. Men with Prostate Imaging Reporting and Data System (PI-RADS) ≥3 lesions based on PI-RADS v2 were included. Outcome measurements and statistical analysis: Patients were analyzed for potential treatment by FT and hemiablation. MRI lesions were mapped according to prostatic zones. Results and limitations: In total, 2371 patients were analyzed. According to consensus criteria (biopsy-proven unifocal lesion of International Society of Urological Pathology [ISUP] grade group ≤2, prostate-specific antigen [PSA] ≤15 ng/mL, and life expectancy >10 yr), 303 patients (12.8%; ISUP 1: n = 148 [6.2%]; ISUP 2: n = 155 [6.5%]) were potential candidates for FT. A maximum PSA level of <10 ng/mL would exclude further 60 (2.5%) of these men. The eligibility for hemiablation is slightly higher (16.2%). Unifocal lesions (n = 288) were equally distributed within the prostate (anteriorly [31%], apically [29%], and dorsally [36%]). Conclusions: With adherence to consensus statements, only a minority of PCa patients present as potential candidates for FT. Distribution of tumor localization suggests the need for different energy modalities to warrant an optimal FT treatment. Patient summary: We analyzed how many men who receive a magnetic resonance imaging–targeted and systematic prostate biopsy are candidates for the experimental focal therapy of the prostate. When following expert recommendations, only a small number of men are potential candidates for this alternative treatment. This study shows that less than one out of seven men is an eligible candidate for focal ablation after combined magnetic resonance imaging–targeted and systematic biopsy. Eligibility for focal therapy was defined as unifocal prostate cancer of International Society of Urological Pathology grade group ≤2 and prostate-specific antigen <15 ng/mL. The potential for hemiablation is slightly higher, with one out of six men being eligible for focal ablation. Modality-specific limitations are not incorporated.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Biopsy; Consensus; Eligibility criteria; Focal therapy; Focal therapy modalities; Hemiablation; Multiparametric magnetic resonance imaging; Partial gland ablation; Patient selection; Prostate neoplasms

Prognostic and Predictive Potential of CCL5 Expression in Muscle-Invasive Bladder Cancer Patients - Smolka, Cedric; Eckstein, Markus; Jung, Rudolf; Lieb, Verena; Sikic, Danijel; Stöhr, Robert; Bahlinger, Veronika; Bertz, Simone; Kehlen, Astrid; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (International Journal of Molecular Sciences, 2024)
Bladder cancer (BC) is the 12th most commonly diagnosed cancer worldwide. Although there are several well-established molecular and immunological classifications, prognostic and predictive markers for tumor cells and immune cells are still needed. Using a tissue microarray, we analyzed the expression of the chemokine CC motif ligand 5 (CCL5) by immunohistochemistry (IHC) in 175 muscle-invasive BC samples. The application of a single cutoff for the staining status of tumor cells (TCs; positive vs. negative) and immune cells (ICs; positive vs. negative) revealed 75 patients (42.9%) and 123 patients (70.3%) with CCL5-positive TCs or ICs, respectively. IHC results were associated with prognostic and predictive data. Multivariate Cox regression analysis revealed that positive CCL5 staining in TCs was associated with significantly shorter disease-specific survival (DSS; RR = 1.51; p = 0.047), but CCL5-negative ICs were associated with significantly shorter overall survival (OS; RR = 1.66; p = 0.005), DSS (RR = 2.02; p = 0.001) and recurrence-free survival (RFS; RR = 1.94; p = 0.002). Adjuvant chemotherapy was favorable for patients with CCL5-negative ICs for OS (RR = 0.30; p = 0.006), DSS (RR = 0.36; p = 0.022) and RFS (RR = 0.41; p = 0.046) but not for patients with CCL5-positive ICs, except in the subgroup of N1 + N2 patients, where it was associated with better OS. We suggest that CCL5 expression can be a prognostic and predictive marker for muscle-invasive bladder cancer patients.
CRIS-Team Scopus Importer:2024-07-12
Keywords: CCL5; chemokine; chemotherapy; immune cells; muscle-invasive bladder cancer; prognosis; tumor cells

Reduced Recurrence Rates Are Associated with Photodynamic Diagnostics Compared to White Light after Extended Transurethral Resection of Bladder Tumors - Marquardt, Alexander; Richterstetter, Mario; Taubert, Helge; Hartmann, Arndt; Wullich, Bernd; Lieb, Verena; Bellut, Laura; Wach, Sven; Apel, Hendrik (Life, 2022)
One pillar in treating non-muscle-invasive bladder cancer (NMIBC) is the complete and high-quality transurethral resection of the primary tumor (TURBT). However, even after a high-quality primary resection, the residual tumor risk is considerable, thus requiring a re-TURBT. Resections performed with the aid of a photodynamic diagnostics report improved recurrence-free survival rates and increased detection rates of carcinoma in situ (CIS). This monocentric retrospective study reports on patients treated with an extended TURBT procedure using conventional white-light cystoscopy or photodynamic diagnostics (PDD). Only patients undergoing a TURBT resection for their primary tumor were included in the statistical analysis. Recurrence-free survival and overall survival were the clinical endpoints. Mann-Whitney U tests and chi-squared tests were used for descriptive intergroup comparisons. The associations with overall survival and recurrence-free survival were determined by univariate and multivariate analyses. The test results were considered significant when p was < 0.05. In comparison to conventional white-light cystoscopy, PDD increased the detection rates of CIS (p = 0.004) and tumor multifocality (p = 0.005) and led to reduced residual tumor incidence at the primary resection site (p < 0.001). Likewise, tumor recurrence rates were reduced in the PDD cohort (p < 0.001). Patient age and the presence of residual tumor at the primary resection site were identified as independent predictors of overall survival. For recurrence-free survival, only the PDD resection method was an independent predictor (HR = 0.43; p < 0.001). In summary, we demonstrated that the utilization of PDD techniques was associated with improved detection rates of CIS and multifocal tumors and with reduced recurrence rates. The extended resection protocol allowed us to determine that PDD resections lead to a reduced residual tumor rate at the initial resection site. This residual tumor state at the resection site, determined by extended TURBT, became an independent predictor of long-term survival. On the other hand, the PDD technique was confirmed as the only independent predictor of recurrence-free survival.
CRIS-Team WoS Importer:2022-06-10